Peran Layanan Advokasi dalam Menangani Kasus Ketidakadilan Pada Peserta Didik - Yora Nurhaliza; Hidayani Syam; Hilma Safni; Idham Khalid (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Advocacy services in guidance and counseling have an important role in protecting students' rights from discriminatory treatment, violence, harassment or other uneducative actions. This research aims to identify the contribution of advocacy services in creating an inclusive and fair school environment. The research was conducted using a library study method with a content analysis approach. The research results show that advocacy services not only help victims regain their rights, but also encourage the creation of a school culture that respects individual dignity. In addition, this service contributes to preventing cases of violations of students' human rights through counselor training, external collaboration, and implementing anti-violence policies. Thus, advocacy services become an important instrument in building a safe and fair educational environment.